Contradictions in Lapita pottery, a composite clone - Ambrose, W. R.
Like the cultures of Neolithic Europe Ñ 'Glockenbecherkultur', 'Trichterbecherkultur', 'Linienbandkeramik' Ñ the 'Lapita culture' of the western Pacific is defined by its distinctive ceramics. What that 'ceramic culture' amounts to in human terms has been a key question in the region's archaeology Ñ complete with a quest for a Lapita homeland. This fresh review focuses on the pottery, the defining stuff itself of the affair.